Visuo-motor integration in unresponsive wakefulness syndrome: A piece of the puzzle towards consciousness detection? - Naro, Antonino (Restor Neurol Neurosci, 2015)
Purpose: The unresponsive wakefulness syndrome (UWS) is characterized by either a profound unawareness or an impairment of large-scale cortico/subcortical connectivity. Nevertheless, some individuals with UWS could show residual markers of consciousness and cognition. In this study, we applied an electrophysiological approach aimed to identify the residual visuomotor connectivity patterns that are thought to be linked to awareness, in patients with chronic disorder of consciousness (DOC). Methods: We measured some markers of visuomotor and premotor-motor integration in 14 patients affected by DOC, before and after the application of transcranial direct current stimulation, delivered over the dorsolateral prefrontal cortex and the parieto-occipital area, paired to transorbital alterning current stimulation. Results: Our protocol induced a potentiation of the electrophysiological markers of visuomotor and premotor-motor connectivity, paired to a clinical improvement, in all of the patients with minimally conscious state and in one individual affected by UWS. Conclusions: Our protocol could be a promising approach to potentiate the functional connectivity within large-scale visuomotor networks, thus allowing identifying the patients suffering from a functional locked-in syndrome (i.e. individuals showing an extreme behavioral motor dysfunction although with somehow preserved cognitive functions that can be identified only through para-clinical tests) within individuals with UWS.